THE PHENOMENON OF BOOK PIRACY IN THE NOVEL “SELAMAT TINGGAL” BY TERE LIYE: FENOMENA PEMBAJAKAN BUKU DALAM NOVEL “SELAMAT TINGGAL” KARYA TERE LIYE - Wira Sakinatun Najahah; Laksmi Laksmi (LLDIKTI Wilayah X, 2022)
This research aims to understand the phenomenon of book piracy from Tere Liye's point of view in one of his novels entitled Selamat Tinggal. This study uses a qualitative methodology through the sociology of literature which emphasizes the sociology of the author and his novel. The results of this study indicate that book piracy is a theft of copyright by book printers, sellers, supported by the large number of buyers of pirated books and the absence of serious legal efforts of this crime. Tere Liye, as an author, creates the novel Selamat Tinggal as a medium of his protest as well as a message to readers of literary works to stop buying pirated books and respect the copyright. Through the story, Tere Liye shows the process of honesty and achieving harmony between speech and action which are summarized in the value of integrity. This is illustrated in the main character's efforts to stop being involved in the pirated bookstore business.